2022
DOI: 10.1371/journal.ppat.1010219
|View full text |Cite|
|
Sign up to set email alerts
|

Itaconate and derivatives reduce interferon responses and inflammation in influenza A virus infection

Abstract: Excessive inflammation is a major cause of morbidity and mortality in many viral infections including influenza. Therefore, there is a need for therapeutic interventions that dampen and redirect inflammatory responses and, ideally, exert antiviral effects. Itaconate is an immunomodulatory metabolite which also reprograms cell metabolism and inflammatory responses when applied exogenously. We evaluated effects of endogenous itaconate and exogenous application of itaconate and its variants dimethyl- and 4-octyl-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 62 publications
(75 reference statements)
3
42
0
Order By: Relevance
“…In addition, the consequences of ACOD1 inhibition may become fully manifest only at the organism level and may not be apparent in cellular models. Indeed, we recently found that CXCL10 expression in IAV-infected bone marrow-derived macrophages did not differ between wild-type and ACOD1 –/– mice, whereas histologically assessed pulmonary inflammation was significantly higher in ACOD1 –/– mice 10 . In contrast to inflammation, low-dose citraconate did have a marked effect on TCA cycle intermediates and tended to improve mitochondrial respiration in dTHP1 cells stimulated with LPS/IFN-γ.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In addition, the consequences of ACOD1 inhibition may become fully manifest only at the organism level and may not be apparent in cellular models. Indeed, we recently found that CXCL10 expression in IAV-infected bone marrow-derived macrophages did not differ between wild-type and ACOD1 –/– mice, whereas histologically assessed pulmonary inflammation was significantly higher in ACOD1 –/– mice 10 . In contrast to inflammation, low-dose citraconate did have a marked effect on TCA cycle intermediates and tended to improve mitochondrial respiration in dTHP1 cells stimulated with LPS/IFN-γ.…”
Section: Discussionmentioning
confidence: 90%
“…Itaconate derivatives are being studied as antiviral compounds and adjunct treatments to modify host responses in viral infections 9 , 10 . We therefore infected dTHP1 and A549 cells with IAV and treated them with non-toxic concentrations of the three isomers, as determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations